ANALISIS KEMAMPUAN MENULIS KARANGAN NARASI DENGAN TEMA PERISTIWA DALAM KEHIDUPAN PADA MUATAN BAHASA INDONESIA - Ardianto, Simun (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
The research was aimed to (1) observe the students’ skill in writing narrative text, (2) find the mistakes in standard Indonesian language of the narrative text on the topic of Life Phenomenon in Indonesian Subject of fifth graders Elementary School. The method applied was quantitative and qualitative, in a form of descriptive by collecting data using test and documentation. The data were obtained from the narrative text of the fifth graders' students SD N 1 Pasinggangan consisted of 31 students. The research showed that most of the students could compose narrative correctly with the mean score of 76, which mean in “good category”. However, there were some mistakes about misspelling or mistake in grammar (252 from 139 collected data). The mistakes were spelling 33.33%, punctuation 22.27%, word decoding 5.16%, mistyping 30.95%, and grammar 3,56% such as prefix, suffix, konfix, and infix 0.40%.